2019
DOI: 10.3390/cancers11010049
|View full text |Cite
|
Sign up to set email alerts
|

Oxymatrine Attenuates Tumor Growth and Deactivates STAT5 Signaling in a Lung Cancer Xenograft Model

Abstract: Oxymatrine (OMT) is a major alkaloid found in radix Sophorae flavescentis extract and has been reported to exhibit various pharmacological activities. We elucidated the detailed molecular mechanism(s) underlying the therapeutic actions of OMT in non-small cell lung cancer (NSCLC) cells and a xenograft mouse model. Because the STAT5 signaling cascade has a significant role in regulating cell proliferation and survival in tumor cells, we hypothesized that OMT may disrupt this signaling cascade to exert its antic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
59
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

5
5

Authors

Journals

citations
Cited by 93 publications
(61 citation statements)
references
References 104 publications
0
59
1
1
Order By: Relevance
“…International Agency for Research on Cancer has considered nickel as one of the carcinogenic agents [ 123 , 124 , 125 ]. Exposing to nickel-containing compounds is correlated with the risk of lung cancer development [ 126 , 127 ].…”
Section: Chrysin and Cancermentioning
confidence: 99%
“…International Agency for Research on Cancer has considered nickel as one of the carcinogenic agents [ 123 , 124 , 125 ]. Exposing to nickel-containing compounds is correlated with the risk of lung cancer development [ 126 , 127 ].…”
Section: Chrysin and Cancermentioning
confidence: 99%
“…Its China Food and Drug Administration number is Z20026868. Active compounds of KAI include astragalus polysaccharides, astragalosides, ginsenosides, ginseng polysaccharide and oxymatfine [12], and various studies have shown that KAI possesses multiply pharmacological effects: (1)inducing tumor cell apoptosis [13,14]; (2)inhibiting tumor cell proliferation, invasion and metastasis [15,16]; (3)increasing the sensitivity of chemotherapy drugs and reducing adverse events caused by chemotherapy [17][18][19]; (4)improving the body's immune function [20][21][22]. In the clinic, Fan et al found that KAI has obtained good curative effect, could ultimately prolong the survival and improve the quality of life, and mainly used in the treatment of multi-cancers, including liver, lung, colorectal cancer, etc.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the mechanism of the effect of paclitaxel on UC is unclear. Paclitaxel, including nabpaclitaxel, is a widely used chemotherapy drug for various cancers, including PC [26][27][28]. However, many studies have reported that the EMT is associated with acquired resistance to chemotherapy drugs [29][30][31], including paclitaxel [32].…”
Section: Discussionmentioning
confidence: 99%